Legal Protection for Home Ownership Loan Debtors of Bank Tabungan Negara for the Delay in the Issuance of Land Certificates After Credit Repayment - Fazila, Raysha Aulia; Putri, Citraresmi Widoretno (Dinasti Research, 2025)
The delay in issuing land title certificates after the repayment of Home Ownership Loans creates legal uncertainty and potential losses for debtors. This study aims to analyze the responsibility of Bank Tabungan Negara and the role of the National Land Agency regarding delays in issuing land title certificates after loan repayment, to assess whether such delays fulfill the elements of default or constitute an unlawful act and to evaluate the forms of legal protection and dispute resolution mechanisms available to debtors. The object of this study is the legal issue related to delays in issuing land title certificates after loan repayment. The research subjects include Home Ownership Loan debtors, Bank Tabungan Negara and the National Land Agency. This study applies a normative legal research method using juridical analysis and case studies. The results indicate that Bank Tabungan Negara bears moral and administrative responsibility in ensuring the rights of debtors, while the National Land Agency plays a role in the issuance of certificates and supervision of the bank’s obligations. Delays in certificate issuance may fulfill the elements of administrative default if negligence occurs in fulfilling obligations by Bank Tabungan Negara. The bank needs to strengthen its internal task force, while the National Land Agency should optimize the implementation of Electronic Mortgage Rights, Electronic Land Certificates and apply a Service Level Agreement to ensure accountability and timeliness of certificate issuance which provides legal certainty and legal protection.